Spatiotemporal analysis of the coordination of economic development, resource utilization, and environmental quality in the Beijing-Tianjin-Hebei urban agglomeration - Han Han (Elsevier, 2021)
Rapid urbanization has produced a series of environmental and resource issues in the Beijing-Tianjin-Hebei urban agglomeration (BTHUA). It is necessary to identify pathways toward sustainable urban development. This study explores the coordination relationship within the economy-resources-environment (ERE) system in the BTHUA during 2008–2017. First, a comprehensive indicator system and a coupling coordination index (CCI) were established to measure the coordination relationship in the ERE system. Second, an obstacle degree model was applied to identify the leading indicators affecting the coordinated development of the ERE system. Our results suggested that: (1) the coupling coordination state of the ERE system in the BTHUA has improved from a low coordination stage to a good coordination stage during the study period; (2) the spatial distribution of the coupling coordination state showed a pattern of better performance in the south and east and worse in the north and west; (3) the percentage of secondary industry in the GDP, percentage of built-up areas in the total land area, and sewage treatment rate were the primary factors that affected the ERE system’s coordination state. This study provides the basis for future work on the environment and resource protection in the capital region of China and other similar areas undergoing urban sprawl around the world.